Marknadsundersökning för SCA Skog AB avseende utbor i Mälardalen - Wahlquist, Fredrik (2009)
The need of raw material does of course fluctuate but the long term view is an increasing demand due to the growing consumption of sawn timber products, pulp, paper and lately also biomass. This has led to a keener competition for wood. At the same time there is an ongoing structural change of a significant part in the Swedish wood supply market, the private forest owners. In 1992, 22 % of Sweden´s 335 000 private forest owner lived apart from their forest. In 2007 this figure had risen to 36 %. SCA Skog acquires a substantial part of its wood consumption from the private sector and distant forest owners constitutes 38 % of all private owned forest properties in northern Sweden. The primary aim of this report is to make a survey of distant foreign owners, with their forests within SCA´s operational district, who has settled in Mälardalen and to outline a future market approach to this group. There are about 2 500 such distant forest owners in this part of the country. All together they own approximately 185 000 hectares of forest representing a vast amount of wood. Svensk skogsindustris behov av råvara följer givetvis konjunkturen och kan periodvis variera, men över tiden är den långsiktiga trenden att råvarubehovet ökar som en följd av en allt större förbrukning av sågade trävaror, massa, papper och på senare tid även biobränsle. Till detta kommer politiska naturvårdsambitioner. Det här har utmynnat i en hårdare konkurrens om veden, en konkurrens som har förstärkts av att den svenska råvaran varit förhållandevis billig och därmed inbjudit även utländska virkesaktörer. Konkurrensen kan med tiden öka ytterligare om tullarna på ryskt importvirke införs fullt ut. Parallellt med att efterfrågan på virke etablerar sig på en hög nivå sker det strukturella förändringar i den privata skogsägarkåren som en följd av att landsoch skogsbygderna successivt avfolkas och inflyttning sker till städerna. En konsekvens av detta är att allt fler skogsfastigheter betraktas som utbofastigheter, det vill säga att ägaren bor i en ...